Inverse regulation of serum osteoprotegerin and tumor necrosis factor-related apoptosis-inducing ligand levels in patients with leg lesional vascular calcification: An observational study - Moon, Ae Ran (Medicine (Baltimore), 2019)
We hypothesized that circulating osteoprotegerin (OPG) and tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) levels could be associated with vascular calcification, which is predominant in diabetes. The study included 71 Korean participants (36 with diabetes and 35 without diabetes), who were sub-grouped according to the results of the ankle–brachial index (ABI) and/or X-ray computed tomography scan (CT scan). Serum OPG and TRAIL levels were assayed using the respective enzyme-linked immunosorbent assay kits. Statistical significance was analyzed using Student's t test between the 2 groups or analysis of variance (ANOVA) among the 4 groups. Serum OPG was up-regulated in the participants with diabetes, with peripheral arterial disease (PAD), and/or with vascular calcification. TRAIL down-regulation was more strictly controlled than OPG up-regulation; it was significantly downregulated in the participants with PAD and vascular calcification, but not in the participants with diabetes. Serum OPG and TRAIL were regulated in the participants with femoral, popliteal, and peroneal artery calcification but not in the participants with aortic calcification. OPG up-regulation and TRAIL down-regulation were found to be associated with leg lesional vascular calcification; therefore, the average OPG/TRAIL ratio was significantly increased by 3.2-fold in the leg lesional vascular calcification group.